2021
DOI: 10.3389/fpsyg.2021.786391
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Maternal Beliefs About Infant Crying During the Postpartum Period: Interplay With Infant’s Temperament

Abstract: Infant crying is an important signal for their survival and development, and maternal beliefs about crying predict responsiveness to crying. Most studies have considered caregivers’ reactions to crying to be fixed, and it is unclear how they change with their caregiving experience. Additionally, it has recently been suggested that there is a bidirectional relationship between changes in mothers’ beliefs about crying and infants’ temperament. This study examined that relationship using a longitudinal study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The structural changes in the brain, with volume reductions in multiple regions from pregnancy to the postpartum period ( Hoekzema et al, 2017 ), also recover postpartum, suggesting a return to the pre-pregnancy state ( Kim et al, 2010 ; Luders et al, 2020 ). Both other-oriented and self-oriented types of empathy toward infant crying exist and it has been shown that parent-oriented beliefs increase compared with empathy oriented toward infant emotions ( Hiraoka et al, 2021 ). The decrease in bias observed in our study may reflect the early stages of these adaptive processes, including improved cognitive function and reduced bias toward infant stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural changes in the brain, with volume reductions in multiple regions from pregnancy to the postpartum period ( Hoekzema et al, 2017 ), also recover postpartum, suggesting a return to the pre-pregnancy state ( Kim et al, 2010 ; Luders et al, 2020 ). Both other-oriented and self-oriented types of empathy toward infant crying exist and it has been shown that parent-oriented beliefs increase compared with empathy oriented toward infant emotions ( Hiraoka et al, 2021 ). The decrease in bias observed in our study may reflect the early stages of these adaptive processes, including improved cognitive function and reduced bias toward infant stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, certain factors might modulate the trajectory of these changes. For instance, Hiraoka et al (2021) identified varied paths in caregivers’ perceptions regarding infant crying, partly influenced by the infant’s inherent temperament, specifically surgency. Neural responses to infant crying can change depending on the mode of delivery and breastfeeding ( Swain et al, 2008 ; Kim et al, 2011 ), and postnatal interventions have been shown to reduce parenting stress, leading to changes in brain functional connectivity ( Swain et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations